2014
DOI: 10.1128/mbio.01163-14
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Acinetobacter baumannii Genes Necessary for Persistence in the Lung

Abstract: Acinetobacter baumannii is a Gram-negative bacterium that causes diseases such as pneumonia, bacteremia, and soft tissue infections in hospitalized patients. Relatively little is known about how A. baumannii causes these infections. Thus, we used insertion sequencing (INSeq), a combination of transposon mutagenesis and massively parallel next-generation sequencing, to identify novel virulence factors of A. baumannii. To this end, we generated a random transposon mutant library containing 150,000 unique inserti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
226
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(235 citation statements)
references
References 51 publications
(67 reference statements)
8
226
1
Order By: Relevance
“…Direct experimental approaches are not feasible for human gut symbionts, but rodent models have been used with considerable success (2-7). Several pathogens have been examined using Tn-seq in vivo, within different tissue types (38,(41)(42)(43). Some critical mechanisms for S. alvi colonization of the bee gut, including LPS modifications, membrane integrity components, the stringent response, proteases, and DNA break repair, are also important for infection by human pathogens (41)(42)(43).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct experimental approaches are not feasible for human gut symbionts, but rodent models have been used with considerable success (2-7). Several pathogens have been examined using Tn-seq in vivo, within different tissue types (38,(41)(42)(43). Some critical mechanisms for S. alvi colonization of the bee gut, including LPS modifications, membrane integrity components, the stringent response, proteases, and DNA break repair, are also important for infection by human pathogens (41)(42)(43).…”
Section: Resultsmentioning
confidence: 99%
“…Several pathogens have been examined using Tn-seq in vivo, within different tissue types (38,(41)(42)(43). Some critical mechanisms for S. alvi colonization of the bee gut, including LPS modifications, membrane integrity components, the stringent response, proteases, and DNA break repair, are also important for infection by human pathogens (41)(42)(43). Similarly, colonization of light-producing organs by the squid symbiont Vibrio fisheri depends on genes dictating biofilm formation and cellular stress responses (44).…”
Section: Resultsmentioning
confidence: 99%
“…How A. baumannii partitions a given carbohydrate repeat unit to the protein glycosylation pathway or capsule production remains to be determined. Although the carbohydrate structures produced by different strains are highly variable, functional studies have shown that capsule production is essential for Acinetobacter survival during infection and growth in serum (32,46,50,51). It was recently reported that capsule production could be increased by the presence of subinhibitory levels of antibiotics, which increased resistance to complement-mediated killing and led to a hypervirulent phenotype in a mouse model of systemic infection (52).…”
Section: Cell Surfacementioning
confidence: 99%
“…Collectively, these findings indicate that the Acinetobacter T2SS is a previously unrecognized virulence factor mediating pathogenesis in a relevant mammalian model. Interestingly, a recent study by Wang et al utilized an A. baumannii ATCC 17978 gspN mutant for validation of their insertion sequencing murine pulmonary infection studies, and they subsequently found that the gspN mutant did not display any virulence defect in survival or competition models, compared to the parent strain (51). Although these data are in contrast to the newly defined role of type II secretion in Acinetobacter, it was demonstrated previously that gspN homologs were not required for a functioning T2SS in Klebsiella oxytoca (73); furthermore, gspN homologs are absent from numerous known T2SSs in other Gram-negative bacteria (74), indicating the dispensable nature of GspN in functioning T2SSs.…”
Section: Protein Secretionmentioning
confidence: 99%
“…baumannii research progress has been limited by the technologies and resources available for studying the pathogen. Although methods for targeted gene disruption, transposon mutagenesis, single-copy complementation using Tn7, and plasmid complementation have been developed (25)(26)(27)(28)(29)(30)(31), only a few resources have been described for genome-scale experimental studies (31). To facilitate large-scale genetic analysis of A. baumannii, we report here a set of genetic and genomic resources based on a …”
mentioning
confidence: 99%